Технология управления развитием высшего образования на основе внебюджетного финансирования - Чередниченко, Ольга Юрьевна; Лютенко, Ирина Викторовна (Національний аерокосмічний університет ім. М. Є. Жуковського "Харківський авіаційний інститут", 2009)
Работа посвящена вопросам управления развитием системы высшего образования. Рассмотрены основные принципы решения задач управления развитием как с точки зрения государственных механизмов регулирования, так и с учетом привлечения внебюджетных источников финансирования. Отмечено, что одним из перспективных направлений в решении проблем финансового обеспечения сферы образования является развитие внебюджетных инвестиционных фондов. Предложена общая схема технологии управления развитием высшего образования. Рассмотрены задачи управления на уровне инвестиционного фонда.

Given work is devoted to management questions of higher education system developmant. Main principles of developmant management problem solving both from the point of goverment regulation mechanisms and taking into account an attraction of off-budget financing sources were considered. It was noticed that one of the perspective direction in the problems decision of financial maintenance of education is developmant of off-budget investimant funds. The genersl scheme of management technology of higher education development is offered. Management problems at level of investimant fund are considered.
Technology of managemant of higher education development on the basis off-budget financing
Keywords: качество образования; инвестиции; инвестиционный фонд; метод решения задач; development management; higher education; quaity of education; off-budget financing; investments; technology